Identification of Highly Cross-Reactive Mimotopes for a Public T Cell Response in Murine Melanoma - Grace, Beth E.; Backlund, Coralie M.; Morgan, Duncan M.; Kang, Byong H.; Singh, Nishant K.; Huisman, Brooke D.; Rappazzo, C. Garrett; Moynihan, Kelly D.; Maiorino, Laura; Dobson, Connor S.; Kyung, Taeyoon; Gordon, Khloe S.; et al. (Frontiers in Immunology, 2022)
While immune checkpoint blockade results in durable responses for some patients, many others have not experienced such benefits. These treatments rely upon reinvigorating specific T cell-antigen interactions. However, it is often unknown what antigens are being recognized by T cells or how to potently induce antigen-specific responses in a broadly applicable manner. Here, we characterized the CD8+ T cell response to a murine model of melanoma following combination immunotherapy to determine the basis of tumor recognition. Sequencing of tumor-infiltrating T cells revealed a repertoire of highly homologous TCR sequences that were particularly expanded in treated mice and which recognized an antigen from an endogenous retrovirus. While vaccination against this peptide failed to raise a protective T cell response in vivo, engineered antigen mimotopes induced a significant expansion of CD8+ T cells cross-reactive to the original antigen. Vaccination with mimotopes resulted in killing of antigen-loaded cells in vivo yet showed modest survival benefit in a prophylactic vaccine paradigm. Together, this work demonstrates the identification of a dominant tumor-associated antigen and generation of mimotopes which can induce robust functional T cell responses that are cross-reactive to the endogenous antigen across multiple individuals.